Thiopurines: Recent Topics and Their Role in the Treatment of Inflammatory Bowel Diseases - Keiichi Tominaga; Takeshi Sugaya; Takanao Tanaka; Mimari Kanazawa; Makoto Iijima; Atsushi Irisawa (Frontiers Media S.A., 2021)
Ulcerative colitis (UC) and Crohn's disease (CD) are chronic inflammatory bowel diseases (IBD) of unknown etiology, characterized by repeated relapse and remission. The efficacy of thiopurine in IBD was first reported in the late 1960s. Thiopurines are used to alleviate the symptoms of IBD, especially UC. These drugs have a steroid-sparing potential and are widely used for the purpose of maintaining long-term remission in steroid-dependent cases. Therefore, thiopurines tend to be used long-term, but adverse events that accompany long-term use, such as lymphoproliferative disorders, must be monitored with care. In contrast, thiopurine plays a critical role in controlling the immunogenicity of biologics. Furthermore, although thiopurine is an old drug, new findings, including the prediction of serious adverse events such as severe alopecia and acute advanced leukopenia, by nudix hydrolase 15 gene polymorphism analysis, as well as the possibility of appropriate drug monitoring by detailed analysis of 6-thioguanine nucleotides have been clarified. However, the consequences of thiopurine withdrawal have not been determined and further studies, including randomized controlled trials, are necessary to answer the clinical question regarding the scenarios in which thiopurine withdrawal is possible.